Organizational readiness for implementing clinical decision support tools in chronic pain care: a mixed methods evaluation - Reid, Miranda J.; Gutta, Jyotsna; Ellis Hilts, Katy; Knight, Magda; DiIulio, Julie; Bilello, Lori; El Hayek, Mario; Nguyen, Khoa A.; Harle, Christopher A.; Salloum, Ramzi G. (Frontiers in Health Services, 2025)
IntroductionClinical decision support (CDS) tools have the potential to enhance treatment outcomes in chronic pain care, yet their successful implementation depends on the readiness of both providers and clinical staff. The purpose of this study was to assess the readiness for a CDS tool and identify implementation strategies.MethodsA mixed methods approach combined Organizational Readiness for Implementing Change (ORIC) surveys (n = 24 providers; n = 31 clinical staff) and semi-structured interviews (n = 7 providers; n = 3 clinical staff). Quantitative data were analyzed using descriptive statistics and inferential tests, while qualitative data were coded using a rapid qualitative analysis approach.ResultsBoth the ORIC surveys and semi-structured interviews revealed high perceived organizational readiness for implementation across clinics and roles. There was variation in change efficacy, commitment to change, and overall readiness by clinics (p > 0.05) and between roles (p < 0.01), with providers demonstrating statistically significant lower ORIC scores than clinical staff. The qualitative results added nuance, with participants identifying patient and provider level barriers to implementation (e.g., technological literacy, low relative priority). However, these barriers were perceived as surmountable with implementation strategies (e.g., technological support, training and materials for providers and staff).DiscussionThe study highlights the benefits of a mixed methods approach to assessing the readiness. Variation in ORIC scores can help target support resources to clinics and roles with lower perceived readiness. Interviews provide an essential opportunity to identify local barriers and acceptable implementation strategies to build stakeholder support. Combined, these approaches allow for a holistic approach to inform tailored implementation support.